The informal argumentative letter: a didactic sequence of expression and comprehension written in Primary Education - Martín Hidalgo, Irene; Ortiz de Santos, Rosa; Santamaría-Cárdaba, Noelia; Ortega-Quevedo, Vanessa (Didáctica. Lengua y Literatura, 2019)
This educative intervention proposal comes from the importance of promoting language learning in educational field, with the aim of making available to the student those resources that enable communication. To this end, a didactic sequence has been developed which focuses on two main aspects: reading comprehension and written expression. The activities are based on the micro-skills defined by Cassany, Luna and Sanz (2005), to improve reading comprehension and through the Camps (2003) guidelines for written composition. The results reveal the importance of using different teaching methods so as to improve learners’ ability to understand written texts and to compose them, which are inherently related skills. Finally, the effectiveness of this didactic proposal is demonstrated by its application in the classroom, after having contributed to the learning of the language.